Peculiarities of Regional Strategizing in the Light of the Promising Specialization of Territories - Elena V. Kozonogova; Julia V. Dubrovskaya (Communications of International Proceedings, 2020)
Successful management of the regional development in the EU countries is based on the concept of “smart” specialization and technology of “smart” benchmarking. At the same time, these instruments are based on the need to determine the most promising types of economic activity in terms of their contribution to regional development. In Russia, this task could be implemented by creating interregional clusters - unions, whose enterprises are located on the territories of several constituent entities of the Russian Federation. At the same time, it is believed that the development of a constituent entity of the Russian Federation occurs through the growth of indicators of economic efficiency of enterprises belonging to the interregional cluster. In this work, we tested the hypothesis that the effective operation of an interregional cluster is an important tool for regional strategizing, realizing the potential for the development of promising specialization of territories. Studying the results of the activities of the Russian interregional clusters, as well as the analysis of the geoinformation systems in Russia in the field of regional development, the authors empirically proved the formulated hypothesis, and also substantiated the relevance of creating a platform for finding potential partners in order to build added value chains in different regions, taking into account their specializations.
Keywords: Strategizing; Region; Interregional Clusters; Promising Specialization; “Smart Benchmarking”.